Determining the ventilation rate inside an apartment house on the basis of measured carbon dioxide concentrations – case study - Kapalo, Peter; Vilčeková, Silvia; Domnita, Florin; Bacotiu, Ciprian; Voznyak, Orest (International Conference “Environmental Engineering”, 2017)
In the construction process of modern residential buildings the aim is to achieve maximum comfort within minimum energy consumption. One of the ways to achieve this requirement is the accurate determination of the volumetric air flow rate necessary to ensure the required indoor air quality. The aim of the paper is to present a methodology for determination the volumetric air flow rate on the basis of the results obtained from experimental measurements of carbon dioxide concentrations, which were carried out inside an apartment house lived by a standard family. Based on the measured values, the mass flow rate release of carbon dioxide was calculated. Consequently, the volumetric air flow rate was calculated in two situations, during the day and during the night. The main goal of the paper is to determine the required fresh air flow rate in an occupied room, based on carbon dioxide concentration measurement, in order to maintain a comfortable level of indoor air quality. The calculated air flow rate should optimize a future investment in ventilation equipment in order to choose the proper air handling unit with low operating costs. The aim is not only to improve the energy efficiency of the ventilation system, but also to ensure a healthy indoor environment. Based on the presented research it can be stated that during the sleeping of four family members there is necessary to ensure the fresh air flow rate of 104 m3 per hour.